Influence of HIV-related Knowledge and Anticipated Stigma on Depression of Men Who Have Sex with Men: a Latent Class Analysis - Zhenwei DAI, Mingyu SI, Yijin WU, Xu CHEN, Jiaqi FU, Yiman HUANG, Hao WANG, Weijun XIAO, Fei YU, Guodong MI, Xiaoyou SU (Zhongguo quanke yixue, 2022)
Background Chinese men who have sex with men (MSM) have a higher prevalence of depression than the general population. Long-term depression symptoms could increase the risk of having physical harm, self-harm and suicide. Therefore, depression issues among MSM need to be solved urgently. Objective To explore the latent classes of depression, and the influence of HIV-related knowledge and anticipated stigma on depression among MSM. Methods Usingthe General Information Questionnaire, HIV Knowledge Questionnaire, Anticipated HIV Stigma Scale and 10-item Center for Epidemiologic Studies Depression Scale (CES-D-10) , an online questionnaire survey was conducted from December 2020 to March 2021 via the same-sex social network of Blued7.5. A total of 1396 MSM with HIVinfection or unclear status of HIVinfection were sampled by use of convenience sampling to attend the survey. The latent classes of depressive symptoms were analyzed by latent class analysis. Multinomial Logistic regression analysis was used to explore the correlation of the latent class of depression with HIV-related knowledge or anticipated HIV stigma. Results Finally, 1 394 cases (99.9%.) who returned responsive questionnaires were included. The 10 items of CES-D-10 were taken as observed indicators, and exploratory latent class analysis was employed to identify the latent classes of depression based on model from 1 to 5 classes. The 4-class model was finally selected, and the probabilities of each class were 40.1% (no obvious depression) , 21.6% (possible risk of depression) , 28.0% (possible mild depression) , and 10.3% (possible moderate to severe depression) . The accuracy of the classification was assessed by test for homogeneity according to the cut-off value of CES-D-10 (0=no depression, 1=depression) and the results of latent class analysis (0= no obvious depression and possible risk of depression, 1= possible mild depression and possible moderate to severe depression) , and the result showed that Kappa=0.735 (P<0.001) . Multinomial Logistic regression analysis indicated that a high level of HIV-related knowledge (OR=0.926, P=0.001) , undergraduate attainment or above (OR=0.642, P=0.003) were related to possible risk of depression. The anticipated HIV stigma (OR=1.594, P<0.001) and being married (OR=0.593, P=0.026) were related to possible mild depression. A high level of HIV-related knowledge (OR=0.935, P=0.026) , anticipated HIV stigma (OR=2.239, P<0.001) and no long-term employment (OR=1.518, P=0.045) were related to possible moderate to severe depression. Conclusion The depression in MSM population presented obvious category characteristics, which may be a new idea for tailoring interventions to depression in MSM. Relevant authorities may cooperate with social media to deliver interventions incorporated with HIV-related knowledge and anticipated HIV stigma to prevent and control the development of depression in MSM.